Synthesis of Biopolymers by Condensed Histidine Imide Derivatives with Some Acid Anhydride and Their Crosslink with Acrylonitrite - M.A, Firyal.; M., Assel K. (Journal of Petroleum Research and Studies, 2014)
Histidine as known amino acid was converted to its acid chloride [C1] with thionyl chloride at 0 oC, then reacted with ammonia, the corresponding imide-diamine [C2] was obtained, and then condensed with maleic or methylnadic anhydride. The two novel condensed polymers [C3, C4] were obtained with highly conversion percentage and modified to crosslinked polymers [C5, C6] with acrylonitrile monomer through vinylic group by free radical polymerization. The physical properties of all prepared polymers were studied and characterized by 1H-NMR, FT-IR and UV-visible spectroscopy. The swelling % was calculated. The new Polymers [C3, C4], were synthesized by direct polycondensation to give the new bioactive polymers. The rate of hydrolysis of the prepared polymers was studied in different pH values at 37 oC. Howeve, the crosslinked biopolymers [C5, C6] indicated much more chemical resistance than [C3, C4], and the sustained release was observed as good results in basic medium.